Listening Comprehension Skill: The Forgotten Skill in The Saudi Classrooms - Mahmoud, Salamah Saleem; Oraby, Khaled Khader (Institut Agama Islam Negeri Ponorogo, 2024)
Listening plays a very significant role in language acquisition and language learning. The more input kids and students get, the faster and easier it will be for them to acquire and learn any new language. Unfortunately, over a long period listening didn’t receive enough attention by curricula designers, teachers, and students which affected the output and labelled listening as a difficult skill to teach and understand. This study intends to draw the attention to listening through answering three important questions related to the importance of listening, the challenges that face teaching it and suggestions for enhancing this important skill. To this end, the researchers chose all secondary and intermediate students in Jeddah as a population and fifty male and female students as a sample. A survey of twenty- two items was used as a data collection tool. The findings of the study showed clear enthusiasm for listening comprehension and an urgent need to overcome the challenges and reconsider suggestions to improve this skill including training teachers, facilitating it, and increasing the weight in the schedules. The study recommends giving more attention to listening and including it in any English language test.